Ultrasound Elastography in Musculoskeletal Radiology: Past, Present, and Future - Snoj, Žiga; Wu, C. H.; Taljanovic, M.S.; Dumić-Čule, I.; Drakonaki, E. E.; Klauser, Andrea S. (Seminars in Musculoskeletal Radiology, 2020)
Ultrasound elastography (USE) is becoming an important adjunct tool in the evaluation of various musculoskeletal (MSK) traumatic conditions and diseases, with an increasing number of applications and publications in recent years. This rapidly evolving technique enhances the conventional ultrasound (US) examination by providing information on the elastic properties of tissue alongside the morphological and vascular information obtained from B-mode US and Doppler imaging. Those performing USE must have basic knowledge of its proper imaging techniques and limitations. In this review article, we place the USE in historical perspective and discuss basic techniques and current applications of USE in the evaluation of various traumatic and pathologic conditions of fasciae, nerves, muscles, tendons, ligaments, and MSK soft tissue masses.
Keywords: ultrasound; elastography; musculoskeletal; quantitative imaging; shear deformation